To die for ebook - Baldacci, David (6:20 Man, 2024)
From a #1 New York Times bestselling author, the 6:20 Man returns, this time sent to the Pacific Northwest to aid in a complicated FBI case—and he’s about to come face-to-face with his nemesis, the girl on the train.   Travis Devine has become a pro at accomplishing any mission he's given. But this time it’s not his skills that send him to Seattle to aid the FBI in escorting orphaned, twelve-year-old Betsy Odom to a meeting with her uncle, who’s under federal investigation. Instead, he’s hoping to lay low and keep off the radar of an enemy–the girl on the train. But as Devine gets to know Betsy, questions begin to arise around the death of her parents. Devine digs for answers, and what he finds points to a conspiracy bigger than he could’ve ever imagined.   It might finally be time for Devine and the girl on the train to come face-to-face. Devine is going to find out the difference between his friends and his enemies–and in some cases, they might well be both.